Web user' knowledge and their behavior towards security threats and vulnerabilities - Aldossary, Alia Ahmed; Zeki, Akram M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Most of web users today are university students. They become more familiar with Information Security (IS) because it is a taught course in the university curriculum. However, there are many students whose level of awareness on this subject is still not enough considering the occurrence of security risks and their frequent usage of the internet. Many studies have been conducted to assess students and to raise their level of IS awareness. This study concerns about students' knowledge and their behaviour or action towards IS. This study investigates whether students' knowledge influence positively over their cultural habits of ignoring things in IS environment. This study inspects students' knowledge about risks that face them daily particularly when they deal with their emails, social network accounts, software downloading and installing and public network. This study selected students from two universities from the eastern part of Saudi Arabia (Dammam and King Faisal University). The results of this study confirmed the research questions and indicate that students' knowledge and culture is associated with their behaviour. Students with more knowledge of IS are less exposed to security risks. © 2015 IEEE.